Modeling and simulation for V-shaped stacked graphene nanosheet FETs (GNFETs) for high frequency applications - S. Raj Kumar (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
A new 2D analytical model for the V-shaped Stacked Graphene Nanosheet Field Effect Transistor (GNFETs) is developed in this study. Using suitable boundary conditions, the Linear Approximation Method (LAM) is used to determine the 2D Poisson equation for the first time. To assess the performance of the device, the exact analytical equations for the variables drain current, transconductance, threshold voltage, electric field, and channel potential are derived. The device operates at cryogenic temperatures as a result of the high electron fluxes into the channel caused by the effect of the Nanosheet channel contact with the gate. It offers a significant scaling of device with a large capacity for drive current. With a perpendicular layered structure, the V-shaped Nanosheet achieves low threshold voltage and high transconductance. When TCAD simulation software and analytical model results are compared, a good degree of agreement is obtained.